A cross-sectional study assessing Pro-VC-Be short-form questionnaire in Canada; measuring psychosocial determinants of vaccination behavior in Canadian healthcare professionals - Arnaud Gagneur; David Roy; Catherine Pelletier; Marie-Eve Trottier; Samuel Lemaire-Paquette; Marina Rousseau; Ève Dubé; Pierre Verger (Human Vaccines & Immunotherapeutics)
Vaccine hesitancy poses a significant challenge to worldwide public health and has been exacerbated by the COVID-19 pandemic, leading to heightened polarization and the spread of misinformation. Addressing vaccine hesitancy requires multifaceted strategies in which healthcare professionals (HCPs) play a critical role. Nonetheless, HCPs may also be hesitant toward vaccination. The 31-item original Pro-VC-Be tool, designed to measure the psychosocial determinants of vaccine attitudes in HCPs, was first validated in France, French-speaking Belgian regions, and Quebec (Canada). The validity of a short-form version was evaluated and found to be comparable to that of the long-form. Given differing vaccination recommendations and the changing pandemic context, assessing the tool’s stability among diverse Canadian HCPs is crucial. Relying on the original short version of the Pro-VC-Be tool, a cross-sectional online survey was conducted among various Canadian HCPs (N = 544) to explore the psychosocial determinants that impact vaccination-related behaviors (frequency of general vaccination activity, vaccine recommendations activity, and willingness to recommend vaccines). The findings underscore three crucial dimensions – vaccine confidence, proactive efficacy, and trust in authorities – as robust predictors of positive professional practice and attitudes, and thus globally support the results obtained in previous studies using the Pro-VC-Be tool. HCPs with higher vaccine confidence, high proactive efficacy, and higher trust in authorities were 80% and 180% more likely to recommend vaccines to their patients and 80% more likely to have received a COVID-19 vaccine than other HCPs, respectively. By identifying the root causes of vaccine hesitancy among HCPs, adapted strategies can be developed.